Implication of frequency-dependent protocols in antiarrhythmic and proarrhythmic drug testing. (November 2020) - Nánási, Péter P.; Szabó, Zoltán; Kistamás, Kornél; Horváth, Balázs; Virág, László; Jost, Norbert; Bányász, Tamás; Almássy, János; Varró, András
Abstract: It has long been known that the electrophysiological effects of many cardioactive drugs strongly depend on the rate dependent frequency. This was recognized first for class I antiarrhythmic agents: their Vmax suppressive effect was attenuated at long cycle lengths. Later many Ca 2+ channel blockers were also found to follow such kinetics. The explanation was provided by the modulated and the guarded receptor theories. Regarding the duration of cardiac action potentials (APD) an opposite frequency-dependence was observed, i.e. the drug-induced changes in APD were proportional with the cycle length of stimulation, therefore it was referred as "reverse rate-dependency". The beat-to-beat, or short term variability of APD (SV) has been recognized as an important proarrhythmic mechanism, its magnitude can be used as an arrhythmia predictor. SV is modulated by several cardioactive agents, however, these drugs modify also APD itself. In order to clear the drug-specific effects on SV from the concomitant unspecific APD-change related ones, the term of "relative variability" was introduced. Relative variability is increased by ion channel blockers that decrease the negative feedback control of APD (i.e. blockers of ICa, IKr and IKs ) and also by elevation of cytosolic Ca 2+ . Cardiac arrhythmias are also often categorized according to the characteristic heart rate (tachy- and bradyarrhythmias). Tachycardia is proarrhythmic primarily due to the concomitant Ca 2+ overload causing delayed afterdepolarizations. Early afterdepolarizations (EADs) are complications of the bradycardic heart. What is common in the reverse rate-dependent nature of drug action on APD, increased SV and EAD incidence associated with bradycardia.